Factors Influencing Loss to Follow-up among Human Immunodeficiency Virus Exposed Infants in the Early Infant Diagnosis Program in Phalombe, Malawi - Nkhonjera, Joe (Glob Pediatr Health, 2021)
The efforts to prevent mother to child transmission of HIV in Malawi are impeded by the loss to follow-up of HIV-exposed infants (HEI) in care. Early infant diagnosis (EID) of HEI and linkage to care reduces morbidity and mortality. There has been limited attention to infants who are lost to follow up despite their mothers being compliant to the PMTCT program. This study explored factors that influence loss-to-follow up among HEI in the EID program whose mothers were retained in care for up to 24 months in Phalombe district, Malawi. We conducted a descriptive phenomenological qualitative study from May 2017 to July 2018. We purposively conducted 18 in-depth interviews among HIV positive mothers whose HEI were enrolled in the follow-up program and 7 key informant interviews among healthcare workers (HCW). All interviews were digitally recorded, transcribed, and translated verbatim. Data were analyzed manually using a thematic step-by-step approach. Results showed that retention in care is facilitated by aspirations to have a healthy infant and linkage to a nearer facility to a mother’s place of residency. The barriers to retention were non-disclosure of HIV status, inadequate resources, and support, suboptimal guidelines for, a lack of privacy, and unsynchronized hospital visits between a mother and her baby. The study has shown that successful implementation of EID services requires concerted efforts from various contextualized stakeholders whilst focusing on family-centered care. To maximize retention in EID and innovative ways of reaching mothers and babies through flexible guidelines are urgently needed.